2009
DOI: 10.1590/s0034-72992009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação crítica de 33 pacientes com bócio mergulhante tratados cirurgicamente por cervicotomia

Abstract: The possibility of needing a combined access, with neck and chest incisions makes the treatment of substernal goiter a challenge both in the pre-op and the intraoperative. We hereby, discuss a standardization of the surgical technique to minimize the need for a chest approach, making the substernal goiter a surgically treatable disease, through a single neck incision, and with low indices of complication. Aim: to assess the substernal goiter surgically approach through a neck incision and to analyze the surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…As surgeons, we agree that CT assists with determining potential complications, thoracic gland size, possible difficulties for anesthesia, and the possibility of an extra-cervical procedure to approach RSG [11][12][13] . Several authors have suggested that goiter extension to the level of the aortic arch, especially when associated with tracheal involvement or displacement of a larger vessel, increases the probability of a sternotomy 1,3,10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As surgeons, we agree that CT assists with determining potential complications, thoracic gland size, possible difficulties for anesthesia, and the possibility of an extra-cervical procedure to approach RSG [11][12][13] . Several authors have suggested that goiter extension to the level of the aortic arch, especially when associated with tracheal involvement or displacement of a larger vessel, increases the probability of a sternotomy 1,3,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Retrosternal (or substernal or intrathoracic) goiter (RSG) was first described by Haller in 1749, and it is defined as growth or spread of the thyroid gland below the plane of the thoracic inlet (TI) 1 . The literature classifies RSG as one that presents more than 50% of its mass lying inferior to the thoracic inlet ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 1% of goiters are substernal, accounting for 7% of all mediastinal tumors and for 3-20% of thyroidectomies. In the majority of cases the mass is benign and located in the superior mediastinum (Neves et al, 2009). The exact concept for substernal goiter is not clearly defined, and the literature brings several criteria to classify and define this condition.…”
Section: Substernal Goitermentioning
confidence: 99%
“…Descriptors like retrosternal, substernal, diving, mediastinal, or intrathoracic associated with the term goiter are used to define enlarged thyroid glands that extend past the thoracic inlet. Some authors consider as substernal the cases in which at least 50% of the gland invades the thoracic cavity or cases in which the gland invade the mediastinum, even in the slightest (Neves et al, 2009). Depending on its origin, substernal goiters can be classified as primary or secondary.…”
Section: Substernal Goitermentioning
confidence: 99%
“…As taxas de malignidade, associada ao BR, estão entre 4 e 16%. 18 Em nosso caso, a neoplasia somente foi constatada por meio do exame histopatológico pós-operatório, não interferindo na conduta.…”
unclassified